Artificial Intelligence in Education: Opportunities, Challenges, and Implications for Future Learning - Abd Gafur; Suryo Prabowo; Memet Casmat (Newinera Publisher, 2026)
The development of Artificial Intelligence (AI) has significantly influenced educational transformation by supporting more adaptive, flexible, interactive, and personalized learning. This study aims to analyze the utilization of AI in education, identify its opportunities and challenges, and explain its implications for future learning. This research employed a qualitative approach with a library research design. Data were obtained from scientific journal articles, books, book chapters, proceedings, and relevant academic sources discussing AI in education. The selected literature was mainly focused on recent publications and was analyzed using qualitative descriptive analysis through data reduction, data presentation, and conclusion drawing. Source triangulation was applied to strengthen the credibility of the findings. The results show that AI is utilized in education through adaptive learning systems, intelligent tutoring systems, educational chatbots, automated assessment, learning analytics, and interactive digital media. AI provides opportunities to support personalized learning, improve learning efficiency, expand access to education, strengthen digital literacy, and develop 21st-century skills. However, its implementation also faces challenges, including limited technological infrastructure, low teacher digital competence, digital inequality, academic ethics issues, data privacy concerns, technology dependence, and reduced social interaction. The study also indicates that AI changes the roles of teachers and students, where teachers are increasingly positioned as facilitators, mentors, learning designers, and ethical guides, while students are encouraged to become more independent, critical, and digitally literate learners. Therefore, AI should be integrated into education as a supporting tool that strengthens, rather than replaces, human-centered learning. Its implementation requires adequate infrastructure, continuous teacher training, ethical regulation, and responsible digital literacy development.